2018
DOI: 10.1002/hed.25136
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and prognostic value of long non‐coding RNA in HPV‐negative head and neck squamous cell carcinoma

Abstract: We identified and validated differential expression of 5 lncRNA in HPV-negative HNSCC. Low MEG3 expression was associated with favorable 3-year RFS, although the significance of this finding remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…To date, high linc00152 levels have been detected in many cancers, and the associated mechanisms mediating tumorigenesis are complex and specific. Deregulated linc00152 expression has been observed in head and neck squamous cell carcinoma, in which five types of lncRNAs, including linc00152, are differentially expressed . A previous study by Chen et al involving an analysis of 60 lung cancer tissues by RT‐PCR revealed that linc00152 is expressed significantly more in lung cancer tissue than in normal lung tissue.…”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, high linc00152 levels have been detected in many cancers, and the associated mechanisms mediating tumorigenesis are complex and specific. Deregulated linc00152 expression has been observed in head and neck squamous cell carcinoma, in which five types of lncRNAs, including linc00152, are differentially expressed . A previous study by Chen et al involving an analysis of 60 lung cancer tissues by RT‐PCR revealed that linc00152 is expressed significantly more in lung cancer tissue than in normal lung tissue.…”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 99%
“…To date, high linc00152 levels have been detected in many cancers, [21][22][23] and the associated mechanisms mediating tumorigenesis are complex and specific. Deregulated linc00152 expression has been observed in head and neck squamous cell carcinoma, in which five types of lncRNAs, including linc00152, are differentially expressed.…”
Section: Overexpression Of Linc00152 Enhances Cell Proliferation Imentioning
confidence: 99%
“…Notably, long intergenic non-coding RNA 00152 (LINC00152) has been reported to be increased in numerous types of cancer, including glioblastoma, ovarian cancer, urothelial bladder carcinoma and breast cancer (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…19 It is therefore of interest to ascertain what effects, if any, HPV infection may have upon lncRNAs in HNSCC that could explain the differential prognoses. While previous studies have analyzed differential expression of lncRNA in HNSCC, 20 showed significant negative correlation with lnc-IL17RA-11 but differential expression was not significant (|log2 FC| < 1; P-adj > 0.01). ESR1 exhibited positive correlation (cor = 0.1998, P-adj = 3.63e−05) and E) significant differential expression (|log2 FC| = 1.8067, P-adj = 6.06e-24).…”
Section: Genes Coexpressed With Lncrnas In Hnsccmentioning
confidence: 70%